Anaemia among pregnant women in a rural area of Kancheepuram district, Tamil Nadu - A., Abiselvi; S., Gopalakrishnan; R., Umadevi; R, Rama (International Journal Of Community Medicine And Public Health, 2017)
Background: Anaemia is a major public health problem in developing countries. The vulnerable groups include adolescent girls, pregnant and lactating mothers. Despite several National and International strategies to control anaemia, the magnitude of the problem remains high. Lack of adequate program implementation strategies could be a possible reason for this problem and therefore, we aimed to estimate the prevalence of anaemia among rural pregnant women in our field practice area in Tamil Nadu. Methods: This cross sectional study was carried out among 270 pregnant women registered at our Rural Health Training Centre. All these pregnant mothers gave informed consent to participate in the study. A structured interview schedule was administered and hemoglobin levels were recorded from their Mother Child Protection Card. A mean hemoglobin value was calculated and anaemia was defined as a Hemoglobin level <11 g/dl as per WHO classification. Results: About 48.5% of pregnant women were in the age group of 15-24 years. In this study, 41.5% were found to be anaemic. About 38.1% of the study participants were found to have mild anaemia (hemoglobin level between 10.0-10.9 g/dl), while 1.9% had moderate anaemia (Hb between 7.0 - 9.9 g/dl) and 1.5% had severe anaemia (Hb below 7 g/dl). Conclusions: Anaemia is an imminent public health problem, which requires due attention. It is a social problem, wherein the knowledge and attitudes of the pregnant women deeply influence the disease burden. Adequate measures to address these issues have to be in place as a priority, in order to minimize the magnitude of anaemia.